BeWeB. The cross portal of cultural ecclesiastical heritage - Stefano Russo (JLIS.it, 2014)
BeWeb – online ecclesiastical cultural heritage – is a project to establish a portal dedicated to the cultural and artistic heritage of the Catholic Church, by providing an integrated view of data regarding churches, the artwork and items of worship they contain, library and archive funds of diocesan and religious institutes, with a special focus on cultural, scientific and pastoral care aspects, in order to provide an authoritative tool for users to know more about these extraordinary assets. Our goal is to share the outcome of all activities carried out by dioceses and ecclesiastical cultural institutes to manage and enhance their cultural and artistic heritage, both through the catalogue – which provides a virtual map of buildings, items, cultural institutes, archives, funds and libraries – and also through content creation, by connecting different resources together and helping users find their way through this wealth of material, in order for them to appreciate aspects related to pastoral care and worship, in addition to history and culture. Integrating this kind of information leads to a clearer perception of the Church’s unique cultural heritage, which can be understood only by referring to local contexts that provide users with a fundamental key for interpretation. The digital inventory of ecclesiastical cultural and artistic heritage, that Italian dioceses have been urged to contribute to by the Italian Bishops’ Conference since 1997 – with the support of the National Office for Ecclesiastical Cultural Heritage (UNBCE) acting as coordinator – has led to the creation of a massive digital data bank in the last ten years. The inventory documents an extremely important, sizeable and peculiar cultural heritage, and testifies to the sense of responsibility and spirit of service of dioceses and religious institutes. UNBCE has laid down the methodology, identified strategies, provided means and support in the different work stages, but this project has been and still is a major networking effort, to which each diocese and institute contribute, safeguarding the added value that is given by the close union between information and heritage which, in several online projects, is sometimes undermined. The various inventory projects are the result of intense activity based on specific agreements signed with the Ministry for Cultural Heritage and Activities and respective Central Institutes, to promote filing initiatives that comply with relevant national and international standards, safeguarding filing entities’ specifities. The traditionally active dialogue between UNBCE, Ministry officials and particular Churches has led to the pursuit of shared goals in implementing this ambitious project. Currently, BeWeb hosts the data banks of several Italian dioceses’ historic and artistic heritage, in addition to fact sheets regarding dioceses and cultural institutes (museums, archives and libraries). Over time, it will be enriched with data banks of architectural heritage, archival funds and library assets, thus becoming a cross-sectoral portal of ecclesiastical cultural heritage with and extraordinary potential. BeWeb engages in dialogue on a 360° radius: this project also includes continuous updates and reflections regarding national and international scenarios, through a semantic web, open data and integration with internationally-renowned archives such as VIAF, ULAN, TGN. All this is also made possible by the development of access point control and standardization (authority files).BeWeb’s aim is to provide for different navigation needs: from average users looking for basic information to specialists engaging in more sophisticated searches. BeWeb acts as a mediator between users and cultural institutions, to enhance the Church’s important cultural heritage through greater participation by making communication easier.